The Sweetest Dream: Love, Lies, & Assassination - Palmer, Bryan D. (Labour / Le Travail, 2009)
The article reviews the book, "The Sweetest Dream: Love, Lies, & Assassination," by Lillian Pollak.
Keywords: ASSASSINATION; BOOKS – Reviews; Book reviews; Business And Economics–Labor And Industrial Relations; History–History of North And South America; Nonfiction; Novels; POLLAK; Lillian; SWEETEST Dream: Love; Lies & Assassination; The (Book)